Discovery and Biological Evaluation of Potent and Selective N-Methylene Saccharin-Derived Inhibitors for Rhomboid Intramembrane Proteases - Goel, Parul; Jumpertz, Thorsten; Mikles, David C; Tichá, Anežka; Nguyen, Minh T N; Verhelst, Steven; Hubalek, Martin; Johnson, Darren C; Bachovchin, Daniel A; Ogorek, Isabella; Pietrzik, Claus U; Strisovsky, Kvido; et al. (Biochemistry, 2017)
Rhomboids are intramembrane serine proteases and belong to the group of structurally and biochemically most comprehensively characterized membrane proteins. They are highly conserved and ubiquitously distributed in all kingdoms of life and function in a wide range of biological processes, including epidermal growth factor signaling, mitochondrial dynamics, and apoptosis. Importantly, rhomboids have been associated with multiple diseases, including Parkinson's disease, type 2 diabetes, and malaria. However, despite a thorough understanding of many structural and functional aspects of rhomboids, potent and selective inhibitors of these intramembrane proteases are still not available. In this study, we describe the computer-based rational design, chemical synthesis, and biological evaluation of novel N-methylene saccharin-based rhomboid protease inhibitors. Saccharin inhibitors displayed inhibitory potency in the submicromolar range, effectiveness against rhomboids both in vitro and in live Escherichia coli cells, and substantially improved selectivity against human serine hydrolases compared to those of previously known rhomboid inhibitors. Consequently, N-methylene saccharins are promising new templates for the development of rhomboid inhibitors, providing novel tools for probing rhomboid functions in physiology and disease.
Keywords: Serine Proteases; sacharin; Computer-Aided Design; design s pomocí počítače; serinové proteasy; Humans; HEK293 Cells; Membrane Proteins; Serine Proteinase Inhibitors; lidé; Saccharin; HEK293 buňky; Drug Design; inhibitory serinových proteinas; membránové proteiny; racionální návrh léčiv